2017
DOI: 10.1017/aer.2017.136
|View full text |Cite
|
Sign up to set email alerts
|

Surface integrity generated with peripheral milling and the effect on low-cycle fatigue performance of aeronautic titanium alloy Ti-6Al-4V

Abstract: Machining-induced surface integrity has an important effect on reliability and service life of the components used in the aerospace industry where titanium alloy Ti-6Al-4V is widely applied. Characterisation of machining-induced surface integrity and revealing its effect on fatigue life are conducive to structural fatigue life optimisation design. In the present study, surface topography, residual stress, microstructure and micro-hardness were first characterised in peripheral milling of titanium alloy Ti-6Al-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Meanwhile, it is found that the influence of effective residual stress on the fatigue life of the workpiece is greater than that of the orientational surface topography. Yang et al [103] studied the effect of residual stress on the fatigue life of workpieces during milling of Ti-6Al-4V. The results show that increasing the compressive residual stress can effectively improve the fatigue performance of the workpiece.…”
Section: Fatigue Resistance As Effected By Surface Residual Stressmentioning
confidence: 99%
“…Meanwhile, it is found that the influence of effective residual stress on the fatigue life of the workpiece is greater than that of the orientational surface topography. Yang et al [103] studied the effect of residual stress on the fatigue life of workpieces during milling of Ti-6Al-4V. The results show that increasing the compressive residual stress can effectively improve the fatigue performance of the workpiece.…”
Section: Fatigue Resistance As Effected By Surface Residual Stressmentioning
confidence: 99%
“…For example, Girinon et al [18] realize XRD analyses on the walls of the drilled holes by cutting samples in two semicylinders. Micro-indent mapping is also used to assess the subsurface plasticity related hardening [58,17]. Other authors like Brynk et al [7] choose to measure residual stress by means of digital image correlation (DIC) applied on external surface of drilled holes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is found that the influence of effective residual stress on the fatigue life of the workpiece is greater than that of the orientational surface topography. Yang et al [31] studied the effect of residual stress on the fatigue life of workpieces during milling of Ti-6Al-4V. The results show that increasing the compressive residual stress can effectively improve the fatigue performance of the workpiece.…”
Section: Introductionmentioning
confidence: 99%